Analyses of the thermal behavior, liquid crystal formulations and fatty acid composition of kernel oil as potential detection method for irradiated mango - Chupeco, Tonilou Q. (2004)
ABSTRACT The potential use of the changes in thermal behavior, liquid crystal formations, and fatty acid composition of kernel oil from carabao mango as detection procedure for irradiation was invetigated. The method was comprised of extraction of lipids from the kernel of both non-irradiated and irradiated caraba mangoes; analyses of thermal behavior of the lipid using Differential Scanning Calorimetry and of liquid crystal formations through Optical Polarizing Microscopy; and determination of fatty acid composition using capillary Gas Chromatography-Mass Spectroscopy. Thermal analysis showed that phase transition temperatures of the irradiated kernel lipids were higher than those of the non-irradiated accompanied by reversal in the behavior of the first two peaks. The control had mean peak temperatures at 10.88±0.914°C, 14.92± 1.848°C, and 22.83±0.642°C. On the other hand, the irradiated sample lipid had peaks at 15.45 ± 1.520°C, 21.46±0.644°C, 23.82 ± 0.378°C. The kernel lipids from the irradiated specimens had liquid crystals with lower orientational order compared to those found in the lipids from the non-irradiated specimens. Individual positive units and negative units, fine mosaic texture, and focal conic texture were identified to be present in the non-irradiated sample. On the other hand, the liquid crystals exhibited by the irradiated sample were individual positive and negative units, coarse mosaic texture, and oily streaks. The fatty acids present in appreciable amounts in the non-irradiated mango kernel lipid were hexadecanoic, heptadecanoic, octadecanoic, 9-octadecenoic, 9,12-octadecadienoic, eicosanoic, 11-eicosanoic, docosanoic, tricosanoic, and tetracosanoic acids. However, upon irradiation, nanodecanoic and heneicosanoic acids were present and the amount of hexadecanoic acid and octadecanoic acids decreased accompanied by the formation of a large amount of 9-hexadecenoic acid and an increase in the amount of 9,12-octadecadienoic acid. Results showed the potential use of changes in thermal analysis, liquid crystal formation and fatty acid composition as a rapid method for the detection of irradiation in car